Refractory calcinosis in a patient with dermatomyositis: response to intravenous immune globulin - Shahani, Lokesh (BMJ Case Rep, 2012)
Dermatomyositis is an inflammatory myopathy and commonly presents with progressive, symmetric proximal muscle weakness and cutaneous findings. Calcinosis is a severe manifestation that can be debilitating. The cutaneous manifestations of dermatomyositis may also develop in the absence of detectable muscle disease, and can persist after the successful treatment of myositis. The author reports a 30-year-old woman with biopsy-proven dermatomyositis who had failed previous trials of azathioprine and methotrexate. Her muscle weakness was controlled with mycophenolate mofetil and prednisone; however,  she had recurrent attacks of painful calcinosis. The patient responded to intravenous immune globulin (IVIG) along with intravenous methylprednisone, followed by IVIG for 2 consecutive days each month. This regimen has been effective in preventing recurrence of her calcinosis. This case illustrates the cutaneous manifestation of dermatomyositis, which is often more refractory to treat as compared to the muscle involvement and require additional approaches such as IVIG.